RANCANGAN BANGUN SISTEM INFORMASI ABSENSI DAN SELLOUT PRODUCTS GLICO BERBASIS WEB DENGAN METODE EXTREME PROGRAMMING (STUDI KASUS : SALES PROMOTION GIRL PT GELATIK SUPRA) - Mohammad Salis Pataya; Yono Cahyono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
PT. Gelatik Supra is a company engaged in the field of labor supply (outsourcing), especially Sales Promotion Girl (SPG), Sales Promotion Boy (SPB), Beauty Consultant (International Beauty Products) and MD (Merchandiser). Attendance is an important thing for an agency or company. Attendance is said to be important because it can affect the amount of salary or wages of an employee and from attendance can also see the performance of an employee who is often present or not present.The system for taking employee attendance at PT Gelaltik Supra for the SPG Project Glico, taking attendance and inputting selling out of glico products, the employees are still recording on paper or still using Presence & Daily activity - Rundown. As a result of this final project, a web-based application for the SPG Attendance Information System and PHPbased Selling out is made, the attendance process will be more efficient and can be monitored easily by the Head office. Therefore, to overcome this problem the author uses application design with the application development model is Extreme Programming which is expected to increase a sense of satisfaction to clients, system development can be made faster and establish good communication between developers and clients, by means of interviews. to get user stories, which will later make database design, coding and user interfaces according to the needs of user stories.